Studies in Colombian Caelifera and adjacent territories: Ciglianacris, a new genus of Andean Melanoplinae (Orthoptera: Acrididae) - Cadena-Castañeda, Oscar J.; Granda, Juan Manuel Cardona (Zootaxa, 2017)
A new genus and species of neotropical melanoplines living in the submontane forests of the Colombian Andes is hereby described. This genus is closely related to the genera of the genus group Scotussae and the Andean genera Bogotacris and Chibchacris, distributed in the paramo ecosystems of Colombia and Venezuela.